Revision and phylogenetic analysis of the spider genus Philisca Simon (Araneae: Anyphaenidae, Amaurobioidinae) - Soto, Eduardo M.; Ramírez, Martín J. (Zootaxa, 2012)
We review the spider genus Philisca Simon, an endemic of the southern forests in Chile and Argentina, and present aphylogenetic analysis including 15 species, of which five are newly described (P. atrata, P. robinson, P. viernes, P. pizarroiand P. robusta), together with other 98 representatives of the family Anyphaenidae. Four species names are considerednomina dubia (Clubiona gayi Nicolet, Drassus mirandus Nicolet, Clubiona altiformis Nicolet, P. obscura Simon). Cluiliuschilensis Mello-Leitão is newly synonymized with P. accentifera Simon. The phylogenetic analysis resulted in P.puconensis Ramírez branching off basally in the genus, because of its numerous leg spines and unmodified malechelicerae, all plesiomorphic for the group; the remaining species form two clear groups. The first one, formed by P. hahniSimon, P. tripunctata (Nicolet), P. amoena (Simon), P. hyadesi (Simon) and P. doilu (Ramírez), are grouped by the lossof spines on legs I and II. The second, formed by P. huapi Ramírez, P. ingens Berland, P. ornata Berland, P. accentiferaSimon, P. atrata and four new species endemic to the Robinson Crusoe Island in the Juan Fernández Archipelago, havethe male chelicerae, and in most cases also the endites, modified. In total, six species of Philisca are endemic to JuanFernández, but our dataset is not conclusive for the distinction of alternative colonization scenarios. We analyze theevolution of leg macrosetae, and show two independent instances of reduction of spination, one on the continent and another on the Juan Fernández islands.